THE STATE AND PROSPECTS OF DIGITAL TRANSFORMATION OF UKRAINIAN ECONOMY IN THE CONTEXT OF BUILDING A GLOBAL INFORMATION AND NETWORK SOCIETY - CHERKASHYNA, Tetiana (Herald of Khmelnytskyi National University. Economic sciences, 2025)
In modern conditions there is a rapid spread of electronic and digital technologies that form the basis for the transition to a new stage of the development of world civilization that is digital (information-network or platform) society. In digital society countries will be successful and will receive so-called "digital dividends" if they form the most effective infrastructure of digital economy so the study of theoretical foundations of the formation of digital society and the practical aspects of the country’s digital transformation is an urgent scientific task. The aim of this article is to analyze the state and trends of transformation of Ukrainian economy in the context of formation of global information-network society. In this research, the following scientific methods have been used: analysis, synthesis, induction, deduction, scientific abstraction for analysis and generalization the basic concepts of the subject area and main approaches to the analysis of the country’s digital transformation; statistical method for analysis the digital transformation of Ukrainian economy in 2021-2023 using global indices; graphical analysis for building tables, diagrams and presenting obtained results visually. The author founded that there is dynamic development of information and communication technologies in Ukraine that is explained not only by global trends in digitalization of all spheres of public life of the population but also by the effect of martial law that necessitates the spread of exclusively online services (educational, banking, medical, insurance, accounting, legal, etc.). Despite this the dynamics of all global indices of digitalization of Ukrainian economy was not positive in 2021-2023. As a result, among European countries Ukraine was one of the outsider countries because the value of most global indices was much lower compared to both Western and Northern European countries and Central and Eastern European countries (so-called "post-socialist countries"). The article is an empirical.